JIP: jokes, idioms and proverbs jako wspólny projekt językowy w 24 krajach - Kurth, Urlike (JIP - Jokes, Idioms and Proverbs as a Common Language Project in 24 Countries, 2008)
The article is about the JIP project, which focuses on popular catchphrases, proverbs and clichés. Its aim is to inspire interest in foreign languages, show the similarities and differences between them. It is carried out by partner institution in 24 countries, and thus it is addressed to almost all citizens of the EU. For the right motivation it is not only important to present the collected material in a clear way, but also to have easy access to foreign languages. For presenting cultural differences in particular language structures, selected and most frequently used phrases were chosen, situational expressions used for wishing, catchphrases, proverbs, idioms and normative collocations in different languages.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 158-165